Physiological characteristics of successful mountain bikers and professional road cyclists - Lee, H.; Martin, D. T.; Anson, J. M.; Grundy, D.; Hahn, A. G. (Journal of Sports Sciences, 2002)
The aims of this study were to compare the physiological and anthropometric characteristics of successful mountain bikers and professional road cyclists and to re-examine the power-to-weight characteristics of internationally competitive mountain bikers. Internationally competitive cyclists (seven mountain bikers and seven road cyclists) completed the following tests: anthropometric measurements, an incremental cycle ergometer test and a 30 min laboratory time-trial. The mountain bikers were lighter (65.3+/-6.5 vs 74.7+/-3.8 kg, P= 0.01; mean +/- s) and leaner than the road cyclists (sum of seven skinfolds: 33.9+/-5.7 vs 44.5+/-10.8 mm, P = 0.04). The mountain bikers produced higher power outputs relative to body mass at maximal exercise (6.3+/-0.5 vs 5.8+/-0.3 W x kg(-1), P= 0.03), at the lactate threshold (5.2+/-0.6 vs 4.7+/-0.3 W x kg(-1), P= 0.048) and during the 30 min time-trial (5.5+/-0.5 vs 4.9+/-0.3 W x kg(-1), P = 0.02). Similarly, peak oxygen uptake relative tobody mass was higher in the mountain bikers (78.3+/-4.4 vs 73.0+/-3.4 ml x kg(-1) x min(-1), P = 0.03). The results indicate that high power-to-weight characteristics are important for success in mountain biking. The mountain bikers possessed similar anthropometric and physiological characteristics to previously studied road cycling uphill specialists.